Type series of resonant vibration equipment for concrete mixtures compaction and its main parameters calculation method - V. G. Zedgenizov; S. Kh. Faizov (Вестник СибАДИ, 2023)
Introduction. Increasing the energy efficiency of vibration technology poses a number of challenges for its developers. A promising direction for reducing energy costs for driving vibration machines is the use of the resonance phenomenon. Due to the dynamic properties of the oscillatory system, it is possible to significantly reduce the power consumption of resonant vibration equipment, and in some cases, improve the quality of the products. The purpose of this article is to develop a standard range of resonant vibration equipment for compacting concrete mixtures and a methodology for calculating its main parameters.The object of research is the oscillatory system of a vibrating machine, consisting of two masses connected by the elastic and dissipative elements. In addition, the first mass is connected to a fixed base through elastic and dissipative elements.Materials and methods. The basic principles of theoretical mechanics, mathematical modelling and statistical processing of results were used in the research.Results. According to the research results, it was established that with an increase in the mass ratio of the oscillatory system, the dynamic coefficient decreases, and the width of the resonant zone increases. The regression equations are given. It has been established that with increasing rigidity of the working body, the dynamic coefficient decreases, and the horizontal section on the frequency response, the width of which does not change significantly, shifts to the region of higher frequencies. With an increase in the damping coefficient, the dynamic coefficient decreases, and the width of the resonant zone and the frequency range practically do not change. A wide range of nomenclature and masses of precast reinforced concrete justifies the development of a standard-size range of resonant vibration equipment. A standard range of light (up to 2 tons), medium (2-6 tons) and heavy (6-10 tons) types has been developed. Based on the analysis and generalization of research results, a method for calculating resonant vibration equipment for compacting concrete mixtures has been developed, which makes possible to increase its energy efficiency.